2021
DOI: 10.1080/10463283.2021.1876983
|View full text |Cite
|
Sign up to set email alerts
|

Countering Misinformation and Fake News Through Inoculation and Prebunking

Abstract: There has been increasing concern with the growing infusion of misinformation, or "fake news", into public discourse and politics in many western democracies. Our article first briefly reviews the current state of the literature on conventional countermeasures to misinformation. We then explore proactive measures to prevent misinformation from finding traction in the first place that is based on the psychological theory of "inoculation". Inoculation rests on the idea that if people are forewarned that they mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 341 publications
(256 citation statements)
references
References 113 publications
(147 reference statements)
6
191
0
1
Order By: Relevance
“…However, this negative relation between deaththought accessibility and attention to death-related cues is apparent only in the real news condition and not the fake news condition, which suggests that attempts to suppress conscious death-related thoughts were made upon reading the real news article and not the fake news article. Given that death-thought accessibility was not significantly higher in the real news condition compared to the fake news condition, it is probable that people's prior knowledge of the news article introduced other motivations, such as countering fake news (Are, 2019;Lewandowsky & van der Linden, 2021;Pulido et al, 2020), that could have influenced the attention they pay to deathrelated cues. If participants in the fake news condition knew that the news article they read was fake, it is likely that they would be motivated to identify cues characteristic of fake news instead of ignoring death-related cues to suppress death-related thoughts.…”
Section: Discussionmentioning
confidence: 96%
“…However, this negative relation between deaththought accessibility and attention to death-related cues is apparent only in the real news condition and not the fake news condition, which suggests that attempts to suppress conscious death-related thoughts were made upon reading the real news article and not the fake news article. Given that death-thought accessibility was not significantly higher in the real news condition compared to the fake news condition, it is probable that people's prior knowledge of the news article introduced other motivations, such as countering fake news (Are, 2019;Lewandowsky & van der Linden, 2021;Pulido et al, 2020), that could have influenced the attention they pay to deathrelated cues. If participants in the fake news condition knew that the news article they read was fake, it is likely that they would be motivated to identify cues characteristic of fake news instead of ignoring death-related cues to suppress death-related thoughts.…”
Section: Discussionmentioning
confidence: 96%
“…Lastly, extant reviews of inoculation theory scholarship, in general, have focused nearly exclusively on effects of inoculation messages on direct message recipients (see Compton & Ivanov, 2013; Compton, Jackson, & Dimmock, 2016; Ivanov, 2011; Lewandowsky & van der Linden, 2021). Although much of the focus in inoculation theory has been geared towards understanding the process of cognitive resistance, perhaps the greatest power of inoculation theory messaging lies in its ability to spread and diffuse over populations not initially exposed to the inoculation message (Compton & Pfau, 2009; van der Linden, Maibach, et al., 2017).…”
Section: Inoculation Theory In the Context Of Politicized Sciencementioning
confidence: 99%
“…The majority of inoculation research has relied on so‐called “passive refutations” in which both the counter‐arguments as well as the refutations are provided for the recipient—usually in the form of a conventional persuasive article (Lewandowsky & van der Linden, 2021). McGuire argued, however, that when participants are required to actively generate pro‐and counter‐arguments themselves, this would elicit a more involved cognitive process leading to enhanced resistance (McGuire & Papageorgis, 1961).…”
Section: Inoculation Theory: New Frontiersmentioning
confidence: 99%
See 1 more Smart Citation
“…It posits that pre-emptive exposure to a weakened dose of a persuasive argument can confer resistance against future attacks, much like a medical vaccine builds resistance against future illness (Compton, 2013;McGuire, 1964). A large body of inoculation research across domains has demonstrated its effectiveness in conferring resistance against (unwanted) persuasion (for reviews, see Banas & Rains, 2010;Lewandowsky & van der Linden, 2021), including misinformation about climate change (Cook et al, 2017;van der Linden et al, 2017), conspiracy theories (Banas & Miller, 2013;Jolley & Douglas, 2017), and astroturfing by Russian bots (Zerback et al, 2020).…”
Section: Proactive Approaches: Inoculation Theory and Prebunkingmentioning
confidence: 99%